Design Contributions to the Elaboration of New Modeling Schemes for the Buckling Assessment of Hydraulic Actuators - Florescu, Virgil; Mocanu, Stefan; Rece, Laurenţiu; Motounu, Daniel Cătălin; Gherghina, Aurel; Burlacu, Adrian (Metals (Basel ), 2020)
Hydraulic cylinders represent the main actuating/positioning element for standalone lifting equipment or equipment for various transport platforms. This type of actuator represents a structural component responsible for the operational safety of the equipment it serves. One of the most common and dangerous reasons concerning the end of life for this equipment is the buckling or loss of stability of the elastic equilibrium shape. This article aims to compare the classical approach of the problem in accordance with the strength of materials theory in relation to the numeric algorithms used in the applications for the analysis of structure behavior and the algorithms that are based on the finite element method. The subject of study is a hydraulic cylinder that is installed in a self-lifting platform and because of the manifestation of the phenomenon under analysis, it has led to a technical accident. For this purpose, an estimation of the value for the buckling critical load of the cylinder assembly was carried out.